Domestic service in British Columbia, 1850-1914 - Brown, Lorraine C. (2007)
From the mid 1850s through the early 1900s, the white middle and upper class inhabitants of British Columbia persevered in their attempts to solve the ‘servant problem’ and to re-create the British domestic sphere in a new land. Some families emigrated with their British servants in tow. There were repeated efforts to import English girls and women en masse. And many employers were obliged to tolerate ‘strangers’ (Aboriginal and Chinese servants) in their homes. British Columbia’s peculiar ‘servant problem’ ensured that the Imperial vision of employer-servant relations and domestic order could not be exactly reconstructed.